Malignant melanoma metastasis to sigmoid colon: New endoscopic appearance detected for the first time - Kesici, Uğur (College of Physicians and Surgeons Pakistan, 2020)
Malignant melanoma (MM) develops as a result of malignant transformation of melanocytes. It accounts for 4% of all skin cancers. MM metastases usually occur in regional lymph nodes, bones and central nervous system. In this case report, a case of a 50-year male, who was found to have MM infiltration on colonoscopy performed for the etiology of anemia, is discussed. The patient underwent gastroscopy and colonoscopy for the determination of the primary tumor. Colonoscopic examination showed multiple submucosal hyperpigmented areas and a sessile polyp with a diameter of 4-5 mm in the sigmoid colon. Biopsies of hyperpigmented lesions were consistent with MM infiltration. Gastrointestinal tract (GIT) metastases are rare in MM. In literature, MM metastases to GIT have endoscopic appearances of 3 types. Typically, on endoscopy, ulceration with nodule or mass is visualised. However, in this case, an appearance of 'only submucosal melanosis without mass or nodule' was identified, distinct from previously described three endoscopic views and it was verified histopathologically. This case will help increase awareness of endoscopists in terms of being careful to look for MM metastasis on endoscopic examinations, which may be defined as 4th type of endoscopic appearance.
Keywords: Malignant Melanoma; Metastasis; Colon; Endoscopy